2020
DOI: 10.1016/j.ijbiomac.2020.08.072
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted extraction, characterization and immunomodulatory activity on RAW264.7 cells of polysaccharides from Trichosanthes kirilowii Maxim seeds

Abstract: Microwave-assisted extraction of polysaccharides from Trichosanthes kirilowii Maxim seeds (TKMSP) was optimized using Response surface methodology (RSM) base on Central composite design (CCD). The optimum extraction conditions are detailed as follows: liquid-solid ratio 42 mL/g, extraction temperature 80 °C, microwave power 570 W, extraction time 26 min. Under this conditions, the mean value of TKMSP yield 2.43 ± 0.45% ( n = 3), which was consistent closely with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Neutral red phagocytosis assay was conducted to evaluate the phagocytic capacity of RAW 264.7 cells . After removal of the supernatant, the non-adherent cells were removed by washing twice with PBS.…”
Section: Materials and Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Neutral red phagocytosis assay was conducted to evaluate the phagocytic capacity of RAW 264.7 cells . After removal of the supernatant, the non-adherent cells were removed by washing twice with PBS.…”
Section: Materials and Methodssupporting
confidence: 89%
“…Neutral red phagocytosis assay was conducted to evaluate the phagocytic capacity of RAW 264.7 cells. 34 After removal of the supernatant, the non-adherent cells were removed by washing twice with PBS. Each well was then added with 100 μL of neutral red solution and incubated for 1 h. The solution was discarded, and the cells were washed twice with PBS to remove residual neutral red solution.…”
Section: Introductionmentioning
confidence: 99%
“…In fraction C , the peaks centered at 1650–1600 cm −1 were caused by C=O stretching of free COO-, confirming the presence of uronic acid in AVPG-1 and AVPG-2. In addition, there was a specific peak at 1732.13 cm −1 shown in the spectrum of AVPG-2, which belonged to C=O stretching of methyl-esterified COO- (1760–1730 cm −1 ) [ 33 ]. Generally, the peaks of fraction D between 1200 cm −1 and 1000 cm −1 were called “finger-print” region of polysaccharides.…”
Section: Resultsmentioning
confidence: 99%
“…The area of fraction E below 1000 cm −1 offers more information about the sophisticated structure [ 31 ]. The absorption peak at 853.08 cm −1 indicated that AVPG-1 mainly contained the α configuration [ 33 ]. The characteristic absorptions at 934.76 cm −1 , 853.08 cm −1 and 761.71 cm −1 suggested that AVPG-1was a d -glucopyranose derivative [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The performance of the fitting models was expressed as R 2 correlation, and significant analyses were performed using F -test (Chen et al 2020 ). The values of R 2 , R 2 adj, and CV demonstrated that the model was remarkably significant, reasonable, reproducible, and reliable (Hu et al 2020 ). In addition, the normality assumption was satisfied as to the residual plots approximated along a straight line and the residuals from the least squares fit to show the adequacy of the fitted RSM (Golbargi et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%